2018
DOI: 10.1021/acs.jpca.8b01386
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the C(3P) + Ethylene Reaction: A Trajectory Surface Hopping Study

Abstract: The direct dynamics trajectory surface hopping (DDTSH) method has been employed to study the reaction of C(P) with ethylene (CH). Our trajectory simulations show that at a reagent collision energy of 7.36 kcal/mol, there are two possible product channels: propargyl (HCCCH) + H and carbene (CH) + acetylene (HCCH). Estimated branching ratios based on trajectory propagations indicate that propargyl radical formation is the dominant channel contributing (94.1 ± 5.2) % of the overall products formation with (5.9 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…which has been measured to be rapid down to 15 K (Chastaing et al 1999) and yields propargyl radical as main product, as indicated by extensive experimental and theoretical evidence (Kaiser Bergeat & Loison 2001;Geppert et al 2003;Chin et al 2012;Mandal et al 2018). A second formation pathway, which is also the main route to the two C 3 H 4 isomers, is provided by the dissociative recombination of C 3 H n + ions with electrons…”
Section: Discussionmentioning
confidence: 96%
“…which has been measured to be rapid down to 15 K (Chastaing et al 1999) and yields propargyl radical as main product, as indicated by extensive experimental and theoretical evidence (Kaiser Bergeat & Loison 2001;Geppert et al 2003;Chin et al 2012;Mandal et al 2018). A second formation pathway, which is also the main route to the two C 3 H 4 isomers, is provided by the dissociative recombination of C 3 H n + ions with electrons…”
Section: Discussionmentioning
confidence: 96%
“…In recent past, Li et al investigated the C­( 3 P) + C 3 H 6 reaction and observed that the electrophilic addition of C­( 3 P) to C = C π bond to produce a cyclic ring, followed by ring opening to form trans -CH 3 CHCCH 2 isomer. In our earlier work in studying dynamics of the reaction of C­( 3 P) with C 2 H 4 , we observed three different type of initial approaches without any entrance channel barrier. These three initial approaches are (1) the C­( 3 P) attacks one of the carbon atoms of the ethylene forming very short-lived biradical (ĊCH 2 ĊH 2 ), (2) the C­( 3 P) adds to the C = C π-bond of ethylene yielding c-propylidene, and (3) the C­( 3 P) gets inserted into one of the C – H bonds of the ethylene forming venylmethylene (H 2 C = CHCH).…”
Section: Introductionmentioning
confidence: 96%
“…The reactions of the ground state atomic carbon with hydrocarbons play an important role in combustion, hydrocarbon synthetic chemistry and interstellar chemistry. , In particular, reactions of the ground state atomic carbon are ubiquitous in the dense interstellar clouds, where the temperature ranges 10 to 50 K. Atomic carbon (in the 3 P, 1 D and 1 S electronic states) generally involves in the abstraction of hydrogen, addition to π bond and insertion into a C – H bond reactions with unsaturated hydrocarbons and hetero-organics compounds. Addition of the triplet carbon atom C­( 3 P) to saturated hydrocarbons are less reactive and take place only at high collision energy, but it shows a high reactivity with unsaturated hydrocarbons through a barrier-less addition. The triplet atomic carbon atom primarily attacks the organic molecules containing π bond through electrophilic addition. In recent past, Li et al investigated the C­( 3 P) + C 3 H 6 reaction and observed that the electrophilic addition of C­( 3 P) to C = C π bond to produce a cyclic ring, followed by ring opening to form trans -CH 3 CHCCH 2 isomer.…”
Section: Introductionmentioning
confidence: 99%
“…The propynyl radical holds a C 3 v symmetric point group with an X 2 A 1 electronic ground state and lies 168 kJ mol –1 (0 K) above the propargyl radical. , Literature on the availability and reactivity of 1-propynyl during combustion is scarce. Geppert et al suggested that higher-energy C 3 H 3 isomers like 1-propynyl might represent up to 14% of the total C 3 H 3 yield in crossed molecular beams studies on the reaction of atomic carbon (C­( 3 P)) with ethylene (CH 2 CH 2 ) at a collision energy of 30.8 kJ mol –1 . , However, recent studies on this system were unable to confirm their hypothesis. , Methylacetylene (propyne; CH 3 CCH) could be a source of 1-propynyl radicals, but considering the bond energies of the acetylenic hydrogen bond to those of the acetylene-methyl (C–CH 3 ) and methyl hydrogen bonds (H–C 2 H), the yield would be extremely small . Indeed, hydrogen atom reactions with methylacetylene at combustion-relevant temperatures and pressures produce mainly acetylene by methyl (CH 3 ) displacement, allene (H 2 CCCH 2 ) via hydrogen-assisted isomerization, and the propargyl radical by direct hydrogen abstraction …”
Section: Introductionmentioning
confidence: 99%
“…33,34 However, recent studies on this system were unable to confirm their hypothesis. 35,36 Methylacetylene (propyne; CH 3 CCH) could be a source of 1-propynyl radicals, but considering the bond energies of the acetylenic hydrogen bond to those of the acetylene-methyl (C−CH 3 ) and methyl hydrogen bonds (H−C 2 H), the yield would be extremely small. 37 Indeed, hydrogen atom reactions with methylacetylene at combustion-relevant temperatures and pressures produce mainly acetylene by methyl (CH 3 ) displacement, allene (H 2 CCCH 2 ) via hydrogen-assisted isomerization, and the propargyl radical by direct hydrogen abstraction.…”
Section: Introductionmentioning
confidence: 99%